Condensed-phase laser ionization time-of-flight mass spectrometry of highly energetic nitro-aromatic compounds - Delgado-Pérez, Tomás; Alcántara, José F.; Vadillo-Pérez, José Miguel; Laserna-Vázquez, José Javier (Wiley, 2013)
Rationale: Analysis of explosive compounds represents an interesting field of work due to the obvious social relevance of these compounds. Direct laser ionization allows the analysis of these high internal energy compounds without sampling or preparation procedures. We have studied nitro-aromatic compounds to understand their mass spectra when directly ionized in the condensed phase, different from the gas-phase studies commonly conducted. Methods: Direct condensed-phase laser ionization time-of-flight mass spectrometry of high energy density materials has been performed using a 5 ns width quadrupled Nd:YAG laser. No matrix assistance was used. Fine control of the laser energy allowed the study of the fragmentation processes from values close to the ionization threshold to ones where atomic-only mass spectra were recorded. Results: The influence of the variation of extraction conditions on the recorded mass spectra was investigated. For low extraction width pulses, ions with low m/z values were mainly observed, whereas, at higher widths, higher mass fragment ions were also detected while the total ion current was maintained. Therefore, the mass spectra can be modulated to obtain mass spectra containing molecular or atomic information. The onset of ion generation for the different fragment ions was also studied, yielding information that can help to understand the processes involved in the fragmentation pathways of the molecule and in the dissociation mechanisms. Two sampling procedures allowed the prospective use of LIMS as a screening technique for nitro-aromatic-based highly energetic explosives. Conclusions: Direct analysis of explosive compounds has been performed by laser ionization. A large dependence of the resultant spectra on the laser energy was observed that might be useful for studies of fragmentation pathways. For forensic applications, two sampling procedures might allow the use of LIMS as a screening technique.
Keywords: Ionización; Espectroscopia; Laser ionization; High energy density materials; Explosives